Endovascular treatment in Danon disease: a case report - Jiménez-Bolaños, Rayco; Hernández-Fernández, Francisco; García-García, Jorge; Ayo-Martín, Óscar; del Rey Megias, Laura; Molina-Nuevo, Juan David; Segura, Tomás (Journal of medical case reports, 2024)
Background Danon disease is a lysosomal storage disorder with X-linked inheritance. The classic triad is severe hypertrophic cardiomyopathy, myopathy, and intellectual disability, with different phenotypes between both genders. Ischemic stroke is an uncommon complication, mostly cardioembolic, related to intraventricular thrombus or atrial fibrillation, among others. Case report We report the case of a 14-year-old Caucasian male patient with Danon disease who suffered from an acute ischemic stroke due to occlusion in the M1 segment of the middle cerebral artery. He underwent mechanical thrombectomy, resulting in successful revascularization with satisfactory clinical outcome. We objectified the intraventricular thrombus in the absence of arrhythmic events. Conclusion To our knowledge, we report the first case of ischemic stroke related to Danon disease treated with endovascular treatment.